Genomic Surveillance of SARS-CoV-2 in the Southern Province of Zambia: Detection and Characterization of Alpha, Beta, Delta, and Omicron Variants of Concern - Ben Katowa; Annie Kalonda; Benjamin Mubemba; Japhet Matoba; Doreen Mainza Shempela; Jay Sikalima; Boniface Kabungo; Katendi Changula; Simbarashe Chitanga; Mpanga Kasonde; Otridah Kapona; Nathan Kapata; et al. (Viruses, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) have significantly impacted the global epidemiology of the pandemic. From December 2020 to April 2022, we conducted genomic surveillance of SARS-CoV-2 in the Southern Province of Zambia, a region that shares international borders with Botswana, Namibia, and Zimbabwe and is a major tourist destination. Genetic analysis of 40 SARS-CoV-2 whole genomes revealed the circulation of Alpha (B.1.1.7), Beta (B.1.351), Delta (AY.116), and multiple Omicron subvariants with the BA.1 subvariant being predominant. Whereas Beta, Delta, and Omicron variants were associated with the second, third, and fourth pandemic waves, respectively, the Alpha variant was not associated with any wave in the country. Phylogenetic analysis showed evidence of local transmission and possible multiple introductions of SARS-CoV-2 VOCs in Zambia from different European and African countries. Across the 40 genomes analysed, a total of 292 mutations were observed, including 182 missense mutations, 66 synonymous mutations, 23 deletions, 9 insertions, 1 stop codon, and 11 mutations in the non-coding region. This study stresses the need for the continued monitoring of SARS-CoV-2 circulation in Zambia, particularly in strategically positioned regions such as the Southern Province which could be at increased risk of introduction of novel VOCs.